Evaluasi Perbedaan Kadar Bilirubin Direk pada Individu dengan Riwayat Konsumsi Alkohol dan Tanpa Konsumsi Alkohol - Annisaturrahmah Himawan; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu; Fathurrahman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Direct Bilirubin Is An Important Parameter In Assessing Liver Function, Particularly In Bilirubin Conjugation And Excretion Processes. Long-Term Alcohol Consumption Is Known To Cause Liver Dysfunction, Potentially Increasing Bilirubin Levels In The Blood. This Study Aimed To Evaluate Differences In Direct Bilirubin Levels Between Individuals With A History Of Alcohol Consumption And Non-Consumers. This Study Used An Analytical Observational Method With A Cross-Sectional Approach. The Sample Consisted Of Two Groups: Alcohol Consumers And Non-Consumers, Selected Using Purposive Sampling. Direct Bilirubin Levels Were Measured Using A Spectrophotometric Method. The Results Showed A Difference In Direct Bilirubin Levels Between The Two Groups, With Higher Levels Observed In Alcohol Consumers. Therefore, Alcohol Consumption May Affect Liver Function As Reflected By Increased Direct Bilirubin Levels.